Three-dimensional quantitative evaluation of facial morphology in adults with unilateral cleft lip and palate, and patients without clefts - Othman, S.A.; Ahmad, R.; Asi, S.M.; Ismail, N.H.; Rahman, Z.A. (Elsevier, 2014)
The aims of this study were to assess the quantitative values of measurements using proportion indices in the craniofacial region in patients with repaired, non-syndromic, complete unilateral cleft lip and palate (UCLP), and compare them with a control group who did not have clefts using the non-invasive systems of 3-dimensional technology. Three-dimensional measurements of the facial surfaces of 15 Malay patients who had UCLP repaired and 100 Malay control patients aged 18-25 years were analysed. The 3-dimensional images of the respondents' faces were captured using the VECTRA-3D Stereophotogrammetry System. Eleven craniofacial proportions were assessed using a combination of 18 linear measurements obtained from 21 anthropometric soft tissue landmarks. These measurements were used to produce proportion indices to find the differences in the morphological features between the groups, and assessed using the independent sample t test and z scores. There were significant differences between the groups in 7 out of 11 craniofacial proportion indices (p = 0.001-0.044). Z scores of 2 indices were disproportionate. They were nasal index (which was severely supernormal) and upper lip index (which was moderately supernormal). Patients with UCLP had higher mean z scores, indicating that patients with UCLP tended to have larger faces than the control group. There were clinically important differences mainly in the nasolabial area, where the nose and the upper lip were wider, larger, or flatter in patients with UCLP.